Maternity health professionals' perspectives of cord clamp timing, cord blood banking and cord blood donation: a qualitative study - Lisa Peberdy; Jeanine Young; Debbie Massey; Lauren Kearney (BMC, 2020)
Abstract Background Parents today have several options for the management of their infant's cord blood during the third stage of labour. Parents can choose to have their infant's cord clamped early or to have deferred cord clamping. If the cord is clamped early, cord blood can be collected for private cord blood banking or public cord blood donation for use later if needed. If cord clamping is deferred, the placental blood physiologically transfuses to the neonate and there are physiological advantages to this. These benefits include a smoother cardiovascular transition and increased haemoglobin levels while not interfering with the practice of collecting cord blood for gases if needed. The aim of this study is to explore Australian maternity health professionals' perspectives towards cord clamp timing, cord blood banking and cord blood donation. Methods Fourteen maternity health professionals (midwives and obstetricians) from both private and public practice settings in Australia participated in semi-structured interviews either in person or by telephone. Interviews were transcribed and data analysed using thematic analysis. Results Overall there was strong support for deferred cord clamping, and this was seen as important and routinely discussed with parents as part of antenatal care. However, support did not extend to the options of cord blood banking and donation and to routinely informing parents of these options even when these were available at their birthing location. Conclusion Formalised education for maternity health professionals is needed about the benefits and implications of cord blood banking and cord blood donation so that they have the confidence to openly discuss all options of cord clamp timing, cord blood banking and cord blood donation to facilitate informed decision-making by parents.